74. Brainstem excitability in Hemifacial Spasm and Post-Facial Palsy Synkinesias and effects of botulinum toxin. Issue 12 (December 2017) - Cabboi, M.P.; De Natale, E.R.; Devigili, G.; Lettieri, C.; Pilurzi, G.; Eleopra, R.; Deriu, F.
Abstract : Hemifacial Spasm (HFS) and Post-Facial Palsy Syndrome (PFPS) are characterised by synkinesias which electrophysiological hallmark is the lateral spread of the blink reflex, but functional and anatomical evidence of this phenomenon is lacking. To evaluate brainstem excitability in the facial and trigeminal pathways of the affected and unaffected side in HFS and PFPS and modifications induced by botulinum toxin treatment (BoNT-A). The Blink Reflex (BR), BR Recovery Cycle (BRRC) and Masseter Inhibitory Reflex (MIR) were assessed in HFS ( n  = 10) and PFPS ( n  = 7), before and after BoNT-A. Facial palsy (FP; n  = 4), used as lesional model, and healthy controls (n = 8), were also assessed. BR and MIR were normal in all groups. In all patients BRRC analysis revealed a central hyperexcitability pattern following direct and indirect stimulation on both affected ( p  = 0.000007) and unaffected ( p  = 0.00007) sides, with highest effect at 500 ms interstimulus interval. BoNT-A injection did not affect this pattern in all patient groups. These preliminary results may indicate a brainstem compensatory attempt in response to a facial damage which is severe and temporary in PFPS and subtler but persistent in HFS. Central effects of BoNT-A should be searched at a higher level than the brainstem.